INFLUENCE OF SOCIAL CAPITAL ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN NAIROBI COUNTY KENYA - KAVEE, ESTHER; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Social capital refers connections among individuals, based on norms and networks of cooperation and trust, which spills over to the market and state to enhance collective action between formal actors and achieve improved social efficiency and growth. Despite the significant role by the SMEs it has continued to experience many constraints like poor financial access, lack of innovativeness, limited access to information, unfavourable polices among others that have inhibited the realization of its full potential. The study was guided by the following research objectives which include; finding out to what extent social networks, access to